COMPARING APOLOGIES BETWEEN ENGLISH AND INDONESIAN COMICS - Faizin, Muhammad; Rouf, Sinta Syifani Rahmah; Kurniati, Ruri Fadhilah (ETNOLINGUAL, 2025)
In cross-cultural studies, understanding the nuances of apologies in various languages is crucial to reducing misunderstandings and enhancing interpersonal relationships. This research employs a qualitative method by comparing the speech act of apology in Indonesian and English, focusing on linguistic structures, social contexts, and communication strategies. By analyzing expressions of apology in the Indonesian comic House Daddy and the English comic I Hate That I Love You, the study highlights cultural differences and their impact on the ability to express apologies and repair relationships. The findings reveal similarities and differences: both languages emphasize politeness, tone of speech, and providing reasons in apologies, but differ in gender perspectives, indirect apology strategies, cultural contexts, and intonation expressions. This study contributes to the fields of pragmatics and sociolinguistics by offering insights into how cultural nuances shape communication, with implications for enhancing cross-cultural interactions.